NAVIGATING THE FUTURE: ROBO-ADVISORS IN THE FINANCIAL LANDSCAPE. - Olodude, Rufus Adeoluwa (ABUAD Law Journal, 2024)
Robotic advisors have emerged as a disruptive force in the rapidly evolving financial technology landscape, revolutionizing traditional wealth management practices. Driven by artificial intelligence and automation, these intelligent systems offer investors a novel approach to financial decision-making. This study delves into the multifaceted realm of robotic advisors, examining their development, regulatory framework, challenges, and immense potential in Nigeria. Utilizing a comparative research method, the study meticulously analyzes primary and secondary legal sources to achieve its objectives. Findings reveal that while the legal framework for robotic advisors exists, it remains susceptible to inherent faults and biases. Additionally, the study identifies a degree of human intervention in robotic advisory services, undermining claims of complete autonomy. Based on these findings, the paper advocates for monthly external auditing and independent contractor supervision to enhance investor confidence and security. Furthermore, it recommends regular oversight of human intervention to ensure adherence to regulatory standards. It is anticipated that these recommendations will contribute to restoring confidence and trust in robotic advisory services within the Nigerian landscape.